Gender and its influence on curbing corruption: A case study of China - Wang, Bin; Zainalaludin, Zumilah (Fakulti Ekologi Manusia, Universiti Putra Malaysia, 2023)
Corruption has become a major social and political issue in China since the opening-up reform in 1978 began to be implemented. It is one of the most destructive factors that threatens economic development and growth in developing countries. Since Xi Jinping was appointed president in 2012, the Chinese government has launched an aggressive anticorruption campaign. Amid this anti-corruption campaign, many corruption cases involved women, such as female cadres, mistresses, and family members of male officials. In this paper, five typical cases of women's corruption have been collected from famous/popular or prominent social media sites in China. A causal analysis of women's corruption is then carried out using relevant theories. As a result of women remaining in corruption gangs, relying on family support, or needing promotion or social mobility, they engage in corruption. The cause of these situations can be attributed to gender inequality within traditional cultures and institutions. As a result, gender inequality may contribute to women's corruption. Moreover, females will be more likely to commit corruption if they are unhappy at home